Amalgam Illogical Controller Design Using Amended Moth System for Heat Reduction in Insulated Gate Bipolar Transistor - Loganathan, P.; Selvam, P. (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
The electric vehicle is seen as a possible replacement for current-generation automobiles and to address the rising pollution. In electrical drives, Insulated Gate Bipolar Transistor (IGBT) modules deliver power to the motor generate a lot of heat during switching. However, heat generation in IGBT hinders the performance of the electric vehicle. The foremost existing techniques analyze the heat however does not control the heat production in the IGBT module, and also high heat density leads to failing components. Thus to reduce the heat generated in the IGBT module, the work proposed an amalgam illogical controller that handles nonlinearity and provides a quick response. This controller is further tuned by Amended Moth System (AMS) to reduce heat consumption in the IGBT module with electrical parameters. Furthermore, the IGBT is complex to excessive voltage and excessive temperature therefore the current and voltage harmonics in the inverter are reduced by a seamless genuine adaptive filter that detects and suppresses the specified harmonics in the estimated back-EMF, consequently reducing the harmonic position error in the estimated rotor position. Even though there is a problem with a wide range of frequency in the electric motor. To reduce the switching frequency supremacy harm checker is incorporated which is forced to choose active and zero voltage vectors alternatively, to decrease the variation in the switching frequency. Thus the proposed outcomes efficiently tackle the issues in EV and greatly reduce heat consumption in the IGBT module.The electric vehicle is seen as a possible replacement for current-generationautomobiles and to address the rising pollution. In electrical drives, InsulatedGate Bipolar Transistor (IGBT) modules deliver power to the motor generatea lot of heat during switching. However, heat generation in IGBT hinders theperformance of the electric vehicle. The foremost existing techniquesanalyze the heat however does not control the heat production in the IGBTmodule, and also high heat density leads to failing components. Thus toreduce the heat generated in the IGBT module, the work proposed anamalgam illogical controller that handles nonlinearity and provides a quickresponse. This controller is further tuned by Amended Moth System (AMS)to reduce heat consumption in the IGBT module with electrical parameters.Furthermore, the IGBT is complex to excessive voltage and excessivetemperature therefore the current and voltage harmonics in the inverter arereduced by a seamless genuine adaptive filter that detects and suppresses thespecified harmonics in the estimated back-EMF, consequently reducing theharmonic position error in the estimated rotor position. Even though there isa problem with a wide range of frequency in the electric motor. To reducethe switching frequency supremacy harm checker is incorporated which isforced to choose active and zero voltage vectors alternatively, to decrease thevariation in the switching frequency. Thus the proposed outcomes efficientlytackle the issues in EV and greatly reduce heat consumption in the IGBTmodule.